Dense molecular gas at 12 mm towards Galactic TeV gamma-ray sources. Issue 2 (17th February 2017) - de Wilt, P.; Rowell, G.; Walsh, A. J.; Burton, M.; Rathborne, J.; Fukui, Y.; Kawamura, A.; Aharonian, F.
Abstract: The High Energy Stereoscopic System has revealed many TeV (10 12 eV) gamma-ray sources along the Galactic plane, and around 30 per cent of these sources remain unidentified. The morphology and dynamics of dense gas coincident and surrounding the gamma-ray emission can provide clues about the nature of the TeV emission. The H2 O Southern Galactic Plane Survey (HOPS) undertaken with the Mopra radio telescope includes several dense gas tracers, such as NH3 (n, n) transitions and HC3 N (3–2), star formation tracers including H2 O masers and radio recombination lines that trace ionized gas. A search for dense gas, traced by NH3 (1, 1) emission seen in HOPS and additional observations, towards Galactic TeV sources has been undertaken. Of the 49 Galactic TeV sources covered by 12 mm observations, NH3 (1, 1) is detected towards or adjacent to 38 of them. Dense gas counterparts have been detected near several unidentified Galactic TeV sources that display morphology pointing to a hadronic origin to the TeV gamma-rays. The dense gas detected towards some TeV sources displays unusual emission characteristics, including very broad linewidths and enhanced ortho-to-para NH3 abundance ratios towards HESS J1745−303 and HESS J1801−233, which reflects previous shock activity within the gas.